European Cultural Resources and Regional Development: Pressure and Opportunities From the European Enlargement - Antonio Russo; Jan Van Der Borg (European Regional Science Association (ERSA), 2006)
This paper illustrates the progress the ESPON 1.3.3 project "The Role and Spatial Effects of Cultural Heritage and Identity", started in December 2004 by a network of 12 European Universities under the leadership of Ca' Foscari University of Venice. The conceptual framework of this project lies on the assumption that the cultural heritage of Europe is not just an ensemble of tangible assets to be conserved, but rather an element of dynamism of the territory, affecting trajectories of regional development. Thus the identification and valorisation of the cultural heritage is to be considered an integral component of regional planning, with the potential to increase cohesion within an enlarged European Union. The establishment of an "European identity", gaining from difference and variety, is also part of this vision (Graham et. Al, 2000: 26). In this light, the ESPON 1.3.3 project sets out to highlight the spatial expressions and effects of heritage assets and identify the (existing or potential) elements of territorial coherence at the regional and local scale, mapping the geographical aspects that are actually strengthening regional identities and networks. After introducing a list of regional indicators of the European cultural heritage and identity, reflecting elements such as heritage presence, concentration and diversity, based on the whole NUTS III regional delimitation, the paper addresses the issue of how cultural aspects are related to the main socio-economic trends shaping Europe and affecting regional cohesion. The study highlights existing spatial patterns in such relations, and identifies emerging issues for inclusion of the cultural theme in spatial planning, especially looking at significant areas for cross-border cooperation.
Keywords: 330